Impact of angular pointing error on BER performance of underwater optical wireless links - Boluda-Ruiz, Rubén; García-Zambrana, Antonio; Castillo-Vázquez, Beatriz; Hranilovic, Steve (Optica Publishing Group, 2020)
Even in clear ocean water, underwater optical wireless communication (UOWC) is impaired not only by absorption and scattering, but also by oceanic turbulence and dynamic pointing errors which result in a fading channel, degrading the bit error rate (BER) performance. In this paper, for the first time, we quantify analytically the trade-off between geometric loss and misalignment in underwater scattering channels. A novel geometric loss model is developed which is used to compute the average BER in the presence of absorption and scattering over salinity-induced oceanic turbulence channels. Our findings suggest that UOWC systems are less sensitive to angular pointing errors due to jitter since scattering is able to alleviate such a fading effect at the expense of a higher attenuation due to geometric spread. Monte Carlo simulation results are further included to verify the developed BER expression which is valid over a wide range of signal-to-noise-ratio (SNR). Finally, the impact of inter-symbol interference (ISI) is also quantified by measuring the optical power penalty.
Keywords: Optoelectrónica; Fotónica; Light beams; Oceanic turbulence; Optical signals; Optical wireless communication; Orthogonal frequency-division multiplexing; Phase shift